Mortar formulations with bottom ash from biomass combustion - Modolo, R. C. E.
The management of bottom ashes generated from biomass combustion in bubbling fluidized bed combustors (BFBCs) is a relevant environmental issue due to the increasing volume of production in recent years. In this work, bottom bed ashes from combustion of forest biomass residues in BFBC were used as aggregates in rendering mortar formulations. The ashes were characterized considering their particle size distribution and chemical/phases composition. When compared to conventional calibrated sands used as aggregates, the ashes are composed by particles covering a wider size distribution. SiO2 is the major oxide but CaO content is over 10 wt%, suggesting some cementitious activity that was not confirmed. The amount of chlorides is significant and then water leaching and screening pre-treatment improved the quality of the ashes, despite requiring devoted installation and investment. Mortars produced by replacing commercial sand with equivalent mass of 50 and 190 wt% of ash show similar characteristics to the reference (ash-free) formulation, and satisfied all tested standard specifications. Main worries are caused by the variation of water level of the ashes along the time and the need to control the concentration of chlorides. (C) 2013 Elsevier Ltd. All rights reserved.